Aplikasi Herbisida Ramah Lingkungan pada Kelompok Tani Desa Kungkai Baru Kecamatan Air Periukan Kabupaten Seluma - Risvan Anwar; Djatmiko Djatmiko (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2019)
The Application of Environmentally Friendly Herbicide in Farmers Group of Kungkai Baru Village, Air Periukan Subdistrict, Seluma Regency This service program aimed to overcome the problem of aquatic weeds that disrupt the drainage canal and ponds of farmers without killing non-target organisms. The ultimate goal was that farmers wanted to apply weed control techniques using an effective and environmentally friendly herbicide of Unihaz formulation. The method implemented was a demonstration plot. The location of spraying herbicides was chosen on the drainage channel which was already filled with floating aquatic weeds. The number of plots prepared was 3 plots. Two plots were applied with the Unihaz herbicide formula, while one more was applied with synthetic herbicides made from glyphosate. The dosage used for the herbicide Unihaz formulation is 50 l ha-1, while the synthetic herbicide is 6 l ha-1. The dedication program concluded that the farmer group understood about herbicides that were effective and environmentally friendly. The farmer group has also proven that the herbicide of Unihaz formulation was able to control floating weeds in the drainage channel equivalent to the herbicide containing active ingredients glyphosate.